Optimization of Cinnamon (Cinnamomum zeylanicum Blume) Essential Oil Extraction: Evaluation of Antioxidant and Antiproliferative Effects. (24th December 2019) - Kallel, Imen; Hadrich, Bilel; Gargouri, Bochra; Chaabane, Amina; Lassoued, Saloua; Gdoura, Radhouane; Bayoudh, Ahmed; Ben Messaoud, Ezeddine
Abstract : Having high cytotoxicity cell line effect, Cinnamomum zeylanicum Blume essential oil offers a novel approach to the chemotherapy treatment. In order to enhance its quantity/purity, the experimental conditions to produce essential oil should be more exploited. Steam distillation was used to isolate essential oil, and its conditions' optimization was carried out with the surface-response methodology. The maximum amount (2.6 g/100 g d.b.) was obtained under minimum condensation water flow (0.8 mL/min), a sample size of 6.5 cm, a saline solution concentration of 262.5 g/L, and five washings. The produced essential oil contains >77% of polyphenols. In vitro cytotoxicity was examined using an MTT assay against HeLa and Raji cell lines. The essential oil's capability to inhibit the proliferation of HeLa and Raji cell lines was studied under some conditions presenting IC50 values of 0.13 and 0.57  μ g/mL, respectively. The essential oil was evaluated for its potential as an antioxidant by using in vitro models, such as phosphomolybdenum, DPPH, and H2 O2 methods, in comparison with the synthetic antioxidant BHT (butylated hydroxytoluene) and ascorbic acid (vitamin C) as positive controls. The ammonium phosphomolybdate potency in the present study is of the order of 108.75 ± 32.63 mg of essential oil/equivalent to 1 mg of vitamin C in terms of antioxidant power, and the antioxidant activity of DPPH-H2 O2 was 21.3% and 55.2%, respectively. The Cinnamomum zeylanicum Blume essential oil (CEO) covers important antioxidant and antiproliferative effects. This can be attributed to the presence of few minor and major phenolic compounds.